2001
DOI: 10.1136/fn.84.3.f194
|View full text |Cite
|
Sign up to set email alerts
|

Improved survival and neurodevelopmental outcome after prolonged ventilation in preterm neonates who have received antenatal steroids and surfactant

Abstract: Aims-To assess survival and neurodevelopmental outcome following prolonged ventilation beyond 27 or 49 days of postnatal life in neonates treated with antenatal steroids and surfactant. Methods-The medical records of 84 babies born in 1994-1996 requiring ventilation after 27 postnatal days at Liverpool Women's Hospital were reviewed to determine the duration of mechanical ventilation, survival, and neurodevelopmental outcome at 3 years of age. Results-Fifty six babies were mechanically ventilated after 27 post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 18 publications
1
17
1
Order By: Relevance
“…Long-term outcome is the gold standard for all neonatal interventions and therapy, and further studies should be performed, as suggested by Clark et al [10] and as carried out by Stjernquist and Svenningsen [40], Gaillard et al [12], Kamper et al [25], Hansen et al [16] and Dahl and Kamper [11], for instance.…”
Section: Discussionmentioning
confidence: 97%
“…Long-term outcome is the gold standard for all neonatal interventions and therapy, and further studies should be performed, as suggested by Clark et al [10] and as carried out by Stjernquist and Svenningsen [40], Gaillard et al [12], Kamper et al [25], Hansen et al [16] and Dahl and Kamper [11], for instance.…”
Section: Discussionmentioning
confidence: 97%
“…8,11,15,22,27,96 The incidence of other coexistent morbidities in preterm infants, such as bronchopulmonary dysplasia, intraventricular hemorrhage, necrotizing enterocolitis, nosocomial infections, retinopathy of prematurity, and patent ductus arteriosus, has not changed with surfactant replacement. [2][3][4][5]7,8,22,24 The onset of clinical signs of patent ductus arteriosus may occur earlier, [145][146][147][148] and the incidence of pulmonary hemorrhage, especially in infants of less than 27 weeks' gestation, may be increased.…”
Section: Preterm Infants and Surfactant Effectiveness In Clinical Trialsmentioning
confidence: 99%
“…8,9 Despite surfactant treatment, the risk of respiratory abnormalities later in infancy (recurrent wheezing, asthma, respiratory infection, pulmonaryfunction test abnormalities) and early childhood remains high for preterm infants with respiratory distress syndrome who require mechanical ventilation. [88][89][90][91][92][93][94][95][96][97][98][99] In a small number of patients followed through school age, pulmonary-function studies seem improved by surfactant replacement. 90 Additional long-term respiratoryfunction studies are needed of children who have received surfactant as neonates.…”
Section: Surfactant and Pulmonary Outcomesmentioning
confidence: 99%
“…18,19 Treatment with a double dose of poractant alfa (200 mg/kg) is associated with rapid weaning of oxygen and ventilatory pressures, fewer additional doses, cost benefits, and a survival advantage in comparison with beractant or calfactant. 19 In the present study, beractant and double-dose poractant alfa were randomly used, and both surfactant preparations significantly increased the PO 2 levels and decreased FiO 2 requirements and OI.…”
Section: Discussionmentioning
confidence: 99%